Optimisation of Stingless Bee Honey Nanoemulsions Using Response Surface Methodology - Azri Shahir, Rozman; Norhashila, Hashim; Bernard, Maringgal; Khalina, Abdan (MDPI, 2021)
Nanoemulsions (NEs) have been used in a wide range of products, such as those producedby the food, cosmetics, and pharmaceutical industries, due to their stability and long shelf life. Inthe present study, stingless bee honey (SBH) NEs were formulated using SBH, oleic acid, tween 80,glycerol, and double-distilled water. SBH NEs were prepared using a high-pressure homogeniserand were characterised by observing their stability and droplet size. Fourier Transform-Infrared(FTIR) analysis was used to observe the functional groups of the SBH NEs after being subjected tohigh-pressure homogenisation. Transmission Electron Microscopy (TEM) images were then usedto confirm the particle size of the SBH NEs and to investigate their morphology. The effects ofthe independent variables (percentage of oleic acid, storage time, and storage temperature) on theresponse variables (particle size and polydispersity index) were investigated using the responsesurface methodology, along with a three-level factorial design. The results showed that the modelsdeveloped via the response surface methodology were reliable, with a coefficient of determination(R2) of more than 0.90. The experimental validation indicated an error of less than 10% in the actualresults compared to the predicted results. The FTIR analysis showed that SBH NEs have the samefunctional group as SBH. Observation through TEM indicated that the SBH NEs had a similar particlesize, which was between 10 and 100 nm. Thus, this study shows that SBH NEs can be developedusing a high-pressure homogeniser, which indicates a new direction for SBH by-products.